IGFBP2 plays a key role in aerobic exercise-mediated inhibition of ferroptosis in cardiac ischemia/reperfusion (I/R) injury - Yang, Chenguang; Meng, Xuyang; Xia, Chenxi; Sun, Youjing; Ren, Yirong; Wang, Jun; Li, Yi; Wang, Xiang (Journal of translational medicine, 2025)
Background Ferroptosis is an important mechanism underlying cardiac ischemia/reperfusion (I/R) injury. However, the specific molecular mechanisms by which aerobic exercise alleviates cardiac I/R injury and inhibits ferroptosis remain unclear. Methods In this study, we investigated the effects of IGFBP2 on aerobic exercise-mediated protection of cardiac function following I/R and its influence on ferroptosis in cardiomyocytes and SIRT1 activation. Wild-type (WT) or IGFBP2 knockout (IGFBP2_KO) C57BL/6J mice with I/R injury were subjected to aerobic exercise intervention, and cardiomyocytes exposed to hypoxia/reoxygenation (H/R) were treated with IGFBP2. We explored the role of IGF-1R in IGFBP2-mediated cardiac protection using IGF-1R conditional knockout (IGF-1R_CKO) mice subjected to aerobic exercise intervention and cardiomyocytes exposed to H/R and incubated with IGFBP2 and IGF-1R silenced via adenoviral vector (ADV) transfection. The effects of SIRT1 and TXNIP/TRX on ferroptosis in cardiomyocytes exposed to H/R were also examined using SIRT1 inhibitors, SIRT1 agonists, and adenovirus transfection to modulate TXNIP expression levels. Results Aerobic exercise increased circulating IGFBP2 levels in mice, inhibited ferroptosis in cardiomyocytes, and protected cardiac function following I/R ( p < 0.001). IGFBP2 suppressed ferroptosis in cardiomyocytes subjected to H/R and enhanced SIRT1 activation ( p < 0.001). IGF-1R_CKO abrogated the inhibitory effects of IGFBP2 and aerobic exercise on cardiomyocyte ferroptosis ( p < 0.001). SIRT1 activation inhibited ferroptosis in cardiomyocytes exposed to H/R by downregulating TXNIP expression, upregulating TRX expression, and increasing TXNIP/TRX binding ( p < 0.001). Inhibition of TXNIP suppressed ferroptosis following H/R ( p < 0.001). Conclusion Aerobic exercise-induced circulating IGFBP2 directly interacts with IGF-1R, leading to increased activation of SIRT1 and reduced levels of free TXNIP, thus inhibiting cardiomyocyte ferroptosis in cardiac I/R injury. Graphical abstract